2008
DOI: 10.1186/1471-2466-8-24
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of interstitial lung disease 1995–2005: a Danish nationwide population-based study

Abstract: BackgroundCurrent data on incidence of interstitial lung diseases (ILDs) are sparse and concerns about an increasing trend have been raised. We examined incidence rates (IRs) of ILDs and changes in IRs between 1995 and 2005.MethodsAll persons with a first-time hospital discharge or outpatient diagnosis of ILD were identified through the Danish National Registry of Patients, which covers all Danish hospitals. Crude and age-standardised IRs were computed for ILD overall, as well as stratified by ILD subcategorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 13 publications
4
76
1
9
Order By: Relevance
“…Maher [22] (UK) Kornum [23] (Denmark) (n = 3720) Raghu '06 [2] (USA) (n = 120) Lai [3] (Taiwan) (n = 605)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maher [22] (UK) Kornum [23] (Denmark) (n = 3720) Raghu '06 [2] (USA) (n = 120) Lai [3] (Taiwan) (n = 605)…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, the highest rates were reported in the UK [1,22], with a strong increase over time. Lower rates were noted in Scandinavia [23,33] and southern Europe [36,[38][39][40], although some of these studies were likely subject to under-reporting, and a more recent study from Italy had a higher incidence [14]. In the USA, mortality statistics were lower and estimates using narrow criteria suggested an incidence of 5-8 per 100 000 [2,17,18,30].…”
Section: Overall Incidence and Mortality By Geographic Regionmentioning
confidence: 99%
“…Dodatkowo cytowany raport wskazuje, że nie ma wyczerpują-cych danych na temat ogólnej częstości występowania chorób śródmiąższowych [18]. Współczynnik zapadalności kształtuje się na poziomie 4,1-34,3/100 000 osób w zależności od regionu [19,20]. Rosnącą liczbę zachorowań na śródmiąższowe choroby płuc odnotowano w Danii, gdzie w latach 1998-2002 wartość standaryzowanego współczynnika zapadalności wzrosła z 23,54/100 000 osób do 31,28/100 000 osób [20].…”
Section: Wstępunclassified
“…Uwidocznił się niewielki, lecz systematyczny spadek wartości standa- [20]. Z kolei badania prowadzone w Grecji wykazały niższe wartości wskaźnika (4,6/100 000 populacji) w 2004 r. [27].…”
Section: Omówienieunclassified
“…This may reflect missed cases elsewhere, but the fact that some studies have taken a similar approach and still yielded lower incidences [22,23] suggests there may well be true differences in IPF incidence across regions. There are several possible reasons for this: the latter of two recent studies from Italy with varying estimates speculated about environmental differences such as concentration and sources of environmental pollution [15,23], and studies from Japan have typically shown lower rates which may be due to genetic differences [24,25].…”
mentioning
confidence: 99%